1st Process systems engineering & safety (ProSES) symposium 2019 preface - Ruwaida, Abdul Rasid; Mohamad Rizza, Othman; Noorlisa, Harun; Aainaa Izyan, Nafsun; Mohd Yusri, Mohd Yunus; Zainatul Bahiyah, Handani; Nor Khonisah, Daud (Institute of Physics Publishing, 2019)
The special issue of 1st ProSES Symposium is a collection of invited contributions from the presenters of the inaugural Process Systems Engineering & Safety (ProSES) Symposium, organized by Process Systems Engineering & Safety (ProSES) Research Group, Faculty of Chemical and Process Engineering Technology, formally known as the Faculty of Chemical and Natural Resources Engineering, Universiti Malaysia Pahang, on 4th September 2019 in Kuantan, Pahang, Malaysia. The theme for the 1st ProSES Symposium 2019 is The Role of Modelling and Simulation Towards IR 4.0, since the emergence of IR4.0 technology provides the opportunity for dramatically increasing the reliability and efficiency in production operations of many industrial sectors including chemical-based processing. Hence, it is the aim of this conference to provide the platform for intellectual discourse for the application of computer aided tools for modelling and simulation in the area of process systems engineering and safety particularly in the era of IR4.0, and related topics. 1st ProSES Symposium 2019 attracted more than 60 extended abstracts submissions. Two keynote speakers delivered their particularly interesting topics – Professor Ir Dr Haslenda Hashim from Universiti Teknologi Malaysia with a talk on "Process Modelling and Simulation Toward IR4.0"; and Professor Dr Azmi Mohd Shariff from Universiti Teknologi Petronas on "Process Safety in IR4.0".